Impact of works for taxes on the improvement of the quality of educational service: a case study in the District of Huaral, 2023 - Changana Solis, Ligia Elena (2024)
The Works for Taxes modality has emerged as an innovative strategy to address infrastructure deficiencies in Peruvian schools in the context of education. This modality, regulated by Act 29230, establishes a regulatory framework that promotes collaboration between the public and private sectors, facilitating the financing and execution of initiatives aimed at the optimization of educational facilities. However, it is essential to analyze the real impact of this mechanism on the quality of education offered to the population, beyond the construction or improvement of physical conditions. Therefore, the main objective of this article was the analysis of the impact of works for taxes on the improvement of the quality of educational services in the district of Huaral during the year 2023. Using a descriptive correlation study with a quantitative approach and non-experimental design, the study involved a population of 100 employees and a sample of 80 employees chosen by simple random sampling. The results showed a strong positive correlation (rho = 0.854**) between works for taxes and the improvement of the quality of educational services. This indicates that a greater implementation of these works is related to a better perception of quality by educators and administrators. However, although works for taxes are effective in improving the quality of education, their success is dependent on proper management and efficient allocation of resources in accordance with local needs.